The effect of laser-activated Acidulated Phosphate Fluoride on enamel submitted to erosive solution only: an in vitro prelimnary evaluation - altinok, basak; eren, figen; tanboga, ilknur; peker, sertac; BAKKAL, MELTEM; BAKKAL, MELTEM; peker, fatma (My University, 2011)
Aim The purpose of this in vitro study was to evaluate the potential effect of laser therapy on the prevention of erosive demineralisation either alone or combined with acidulated phosphate fluoride gel on human enamel. It was hypothesized that such a treatment would decrease enamel solubility